Length-weight relationship and condition factor of two cyprinid fishes Squalius squalus and Barbus rebeli from the river Crn Drim in the Republic of the North Macedonia - Jordanova, Maja; Hristovski, Slavčo; Rebok, Katerina; Musai, Musa; Dinevska-Ќovkarovska Suzana; Melovski, Ljupčo (Macedonian Journal of Ecology and Environment, 2020)
In this study, for the first time Length-weight relationship (LWRs) were determined for two fish species: chub Squalius squalus Bonaparte, 1837 and Barbus rebeli Koller, 1926. Fish were collected from the river Crn Drim by electrofishing (Samus 725G) between January 2010 and January 2012. A total 552 specimens were collected. Body weight (W) and total length (L) were measured and weighed and LWRs was estimated as W = a + b∙log(L). The estimated b values were 2.877 and 2.994 for S. squalus and B. rebeli, respectively. No previous information is available for LWRs for those two species, not even in FishBase. The obtained data in this study would be useful for the future ichthyological research of these species.